확장표면을 적용한 액체식 제습기의 열물질 전달 모델링 - 장영수; 이대영 (대한설비공학회, 2011)
This study presents a new idea of liquid desiccant dehumidifier with extended surface to improve the compactness. Extended surface is inserted between vertical cooling tubes, and the liquid desiccant flows down along the tube walls and the extended surface as well. Though the extended surface contributes to the increase in the mass transfer area, the effect tends to be limited because less conductive non-metallic materials need to be applied due to the high corrosiveness of liquid desiccant. To analyze the effects of the extended surface insertion, mathematical modelling and numerical integration are performed for the heat and mass transfer in the liquid desiccant dehumidifier. The results show that, though the liquid desiccant on the extended surface is heated due to the moisture absorption, the temperature can be maintained by periodic mixing at the contact points between the tube and the extended surface with the liquid desiccant stream from the tube side at a relatively low temperature. This implies the absorption heat from the extended surface side can be removed effectively by mixing, which leads to a substantial improvement of the dehumidification in the liquid desiccant dehumidifier with extended surface. When the interval of the extended surface,P_e/L , is less than 0.1, the dehumidification is shown to increase by more than two times compared with that without extended surface.